Cover Feature: The Chiral Twist‐Bend Nematic Phase (N*TB) (Chem. Eur. J. 58/2019). Issue 58 (2nd September 2019) - Walker, Rebecca; Pociecha, Damian; Storey, John M. D.; Gorecka, Ewa; Imrie, Corrie T.
Abstract : The twist‐bend nematic phase (NTB ), in which achiral molecules pack into an overall helical structure, was the first example of spontaneous chiral symmetry breaking in a fluid system. Degenerate helices of opposite handedness are expected in equal numbers, unlike in the chiral nematic phase (N*) formed by chiral molecules, in which only one handedness of helix is present. Introducing molecular chirality into a bent dimeric structure exhibiting the NTB phase—using a (S)‐2‐methylbutyl group—appears to remove this double degeneracy, forming the rarely observed chiral N*TB phase. More information can be found in the Full Paper by R. Walker et al. on page 13329 .